Connective tissue growth factor induces renal fibrosis via epidermal growth factor receptor activation. Issue 2 (10th January 2018) - Rayego‐Mateos, Sandra; Morgado‐Pascual, José Luis; Rodrigues‐Diez, Raúl R; Rodrigues‐Diez, Raquel; Falke, Lucas L; Mezzano, Sergio; Ortiz, Alberto; Egido, Jesús; Goldschmeding, Roel; Ruiz‐Ortega, Marta
Abstract: Connective tissue growth factor (CCN2/CTGF) is a matricellular protein that is overexpressed in progressive human renal diseases, mainly in fibrotic areas. In vitro studies have demonstrated that CCN2 regulates the production of extracellular matrix (ECM) proteins and epithelial–mesenchymal transition (EMT), and could therefore contribute to renal fibrosis. CCN2 blockade ameliorates experimental renal damage, including diminution of ECM accumulation. We have reported that CCN2 and its C‐terminal degradation product CCN2(IV) bind to epidermal growth factor receptor (EGFR) to modulate renal inflammation. However, the receptor involved in CCN2 profibrotic actions has not been described so far. Using a murine model of systemic administration of CCN2(IV), we have unveiled a fibrotic response in the kidney that was diminished by EGFR blockade. Additionally, in conditional CCN2 knockout mice, renal fibrosis elicited by folic acid‐induced renal damage was prevented, and this was linked to inhibition of EGFR pathway activation. Our in vitro studies demonstrated a direct effect of CCN2 via the EGFR pathway on ECM production by fibroblasts and the induction of EMT in tubular epithelial cells. Our studies clearly show that the EGFR regulates CCN2 fibrotic signalling in the kidney, and suggest that EGFR pathway blockade could be a potential therapeutic option to block CCN2‐mediated profibrotic effects in renal diseases. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.